Culturally Diverse Advisory Boards and Volunteers - Lisa A. Guion; Janet Harper Golden; David C. Diehl (EDIS)
Revised! This document is FCS9220, one of a series by Lisa A. Guion and David C. Diehl that includes articles on planning programs to effectively reach diverse audiences. Published by the Family, Youth and Community Sciences Department, June 2010.